Bathyal decapod crustaceans of the Catalan Sea (Northwestern Mediterranean) - Abelló, Pere; Valladares, Francisco José (Museum d'Histoire Naturelle (Marseille), 1988)
[EN] The decapod crustaceans captured during a faunistic survey carried in the Catalan Sea bathyal basin (northwestern Mediterranean) are studied in the present paper. Thirty-nine deep-water trawls were performed between 1 000 and 2 000 m isobaths. Twenty-one decapod crustacean species were identified. The commonest species were Munida tenuimana, Acanthephyra eximia, Aristeus antennatus, Nematocarcinus exilis, Stereosmastis sculpta and Pontophilus norvegicus. Munidopsis tridentata (Anomura: Galatheidae) is recorded for the first time in the Mediterranean. Most species also belong to the North-Atlantic fauna and, even though most of them can also be found in the middle bathyal horizon, the fauna surveyed presents clear differences from that of the latter zone, providing thus evidence to differentiate a middle and a lower assemblages within the deep bathyal mud community [FR] On a etudie les crustaces decapodes captures dans les fonds bathyaux de la Mer Catalane (Mediterranee nord-occidentale a partir de 39 chalutages faits entre les isobathes 1 000 et 2 000 m. On a identifie 21 especes de crustaces decapodes. Les especes les plus communes de l'aire etudiee ont ete Munida tenuimana, Acanthephyra eximia, Aristeus antennatus, Nematocarcinus exilis, Stereomastis sculpta et Pontophilus norvegicus. Munidopsis tridentata (Anomura: Galatheidae) est citee pour la premiere fois en Mediterranee. La plupart des especes appartiennent aussi a la faune nord-atlantique. Bien que beaucoup d'especes puissent etre aussi capturees dans l'horizon bathyal moyen, on a detecte de nettes differences entre ce dernier horizon et l'horizon bathyal profond ici etudie, montrant ainsi la necessite de differencier ces deux horizons (moyen et profond) dans la communaute des vases bathyales